Pembuatan Saluran Drainase di RT 004/RW 006, Kelurahan Karunrung Kecamatan Rappocini Kota Makassar - Abner Tahendrika; Daniel Lallo Pakiding (BADAN PENERBIT STIEPARI PRESS, 2025)
RT 004/RW 006 is one of the residential areas located in Karunrung Urban Village, Rappocini District, Makassar City. This area has a relatively high population density, with most of the land consisting of densely populated housing. The main problem faced by the local community is flooding that frequently occurs during the rainy season. This condition is caused by the existing drainage system, which is no longer able to accommodate the large volume of water during heavy rainfall. Water that should flow smoothly into the main canal slows down, resulting in inundation within the neighborhood. In response to this situation, residents of RT 004/RW 006 collectively took the initiative to construct a new drainage channel. This decision arose from a shared awareness that flooding not only causes material losses but also affects health, comfort, and daily activities. The newly planned drainage channel is designed to be deeper and larger compared to the old one. Its purpose is to allow rainwater to flow more quickly and efficiently into the main canal, thereby reducing the risk of flooding in the area. The construction process involved the active participation of all residents in RT 004/RW 006. Community involvement played an important role, whether in the form of labor, time, or material support. This spirit of cooperation not only demonstrated concern for the environment but also strengthened solidarity and social responsibility in addressing common problems. With the new drainage channel in place, the community hopes that flooding, which has long been a recurring annual issue, can be significantly minimized. Furthermore, residents are committed to maintaining the drainage system to ensure it functions optimally. This includes regular cleaning to prevent blockages and ensuring that the water flow remains unobstructed. Thus, the construction of this drainage system is not merely a technical solution, but also a concrete manifestation of the community’s awareness in preserving the environment and improving collective quality of life.